Bridging the Tenant-Provider Gap in Cloud Services - Jalaparti, Virajith; Ballani, Hitesh; Costa, Paolo; Karagiannis, Thomas; Rowstron, Ant (ACM Symposium on Cloud Computing, 2012)
The disconnect between the resource-centric interface exposed by today’s cloud providers and tenant goals hurts both entities. Tenants are encumbered by having to translate their performance and cost goals into the corresponding resource requirements, while providers suffer revenue loss due to uninformed resource selection by tenants. Instead, we argue for a “job-centric”cloud whereby tenants only specify high-level goals regarding their jobs and applications. To illustrate our ideas, we present Bazaar, a cloud framework offering a job-centric interface for data analytics applications. Bazaar allows tenants to express high-level goals and predicts the resources needed to achieve them. Since multiple resource combinations may achieve the same goal, Bazaar chooses the combination most suitable for the provider. Using large-scale simulations and deployment on a Hadoop cluster, we demonstrate that Bazaar enables a symbiotic tenant-provider relationship. Tenants achieve their performance goals. At the same time, holistic resource selection beneﬁts providers in the form of increased goodput.